2005
DOI: 10.1161/01.cir.0000157737.92938.d8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Race and Mortality and Morbidity After Valve Replacement Surgery

Abstract: Background-Previous studies have shown that black race is an independent predictor of increased operative mortality after coronary artery bypass surgery. Given the higher incidence of hypertension and hypertension-associated left ventricular hypertrophy in blacks, we hypothesized that black race might be associated with increased risk of mortality and morbidity after aortic valve replacement (AVR) or mitral valve replacement (MVR). We could not identify a previous study that used a multivariable model to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 18 publications
9
59
3
1
Order By: Relevance
“…Our single-center, retrospective review of cardiac operations during a 10-year period found that stroke complications were infrequent. The overall stroke rate of 2.8% is similar to that reported in other studies [3][4][5][6][7][8][9][10]19].…”
Section: Commentsupporting
confidence: 88%
“…Our single-center, retrospective review of cardiac operations during a 10-year period found that stroke complications were infrequent. The overall stroke rate of 2.8% is similar to that reported in other studies [3][4][5][6][7][8][9][10]19].…”
Section: Commentsupporting
confidence: 88%
“…4,5,[15][16][17] These studies support our findings that African American race is associated with greater overall morbidity and mortality. Lidor et al 4 studied the impact of race and insurance status on outcomes in patients undergoing surgery for diverticulitis using the Nationwide Inpatient Sample (1999 to 2003).…”
Section: Discussionsupporting
confidence: 76%
“…Finally, this study has not considered other clinically relevant outcomes such as postsurgical complications or survival. Although at least 1 recent article revealed no racial differences in operative mortality for AVR, 37 the significance of these findings must nevertheless be considered in the context of other clinically relevant outcomes.…”
Section: Discussionmentioning
confidence: 93%